Policy innovation through the application of E-government: Case of Bandung championship in assessment information system program - Siti Alia; Elisa Susanti; Idah Wahidah; Fitri Febriani Wahyu; Muhammad Andi Septiadi (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2021)
One of the applications of e-government in Indonesia is the Assessment Information system implemented in the city of Bandung since 2014 where. This e-government innovation is technology-based which makes assessment instruments for leaders and the people of Bandung to assess the performance of the sub-district and village heads. It's just that the lack of community participation makes this application not work according to its function, with qualitative research methods and using the theory of the author's vision to see the readiness of the apparatus and society in implementing this program. This research shows that the performance of the SIP application has not provided the maximum expected output. The not optimal SIP application is due to several factors. There is a need for comprehensive evaluation and improvement, building intensive communication and collaboration between operators and verifiers at the city government and sub-district levels.Keywords: Decision-making, E-Government, Policy Innovation, Readiness, Performance Information System